2022
DOI: 10.1155/2022/1476254
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Surface Plasmon Resonance-Based Biosensor Technologies for Cancer Cell Detection

Abstract: Efforts have been made to enhance the surface sensitivity of the conventional surface plasmon resonance biosensor. To improve the sensitivity, a unique two-dimensional heterostructure layer of titanium disilicide and black phosphorus layer has been deposited over the metal surface. The titanium disilicide (TiSi2) nanosheet is placed in between silver (Ag) and black phosphorus (BP) films in the Kretschmann arrangement. This biosensor executes better over a wide range of refractive index variations, including bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…e sensitivity and detection accuracy are the performance parameters of the biosensor [38], and the same is computed for the proposed biosensor. e sensitivity of the biosensor is represented as S � δθ SPR /δn, where δn is the change in the RI.…”
Section: Resultsmentioning
confidence: 99%
“…e sensitivity and detection accuracy are the performance parameters of the biosensor [38], and the same is computed for the proposed biosensor. e sensitivity of the biosensor is represented as S � δθ SPR /δn, where δn is the change in the RI.…”
Section: Resultsmentioning
confidence: 99%
“…Under TIR circumstances, the photon permeates the metal and passes its energy to oscillating electrons, causing SPR. This happens when the incidence wave vector (Ki) matches the surface plasmon wave vector (Kp) [18]. Light alone can't excite the The suggested biosensor is envisaged to comprise five layers consisting of Figure 1.…”
Section: Methodology and Considerationsmentioning
confidence: 99%
“…Habib et al also reported a hollow-core PhCF sensor with a sensitivity of ≃89% [20]. Moreover, Karki and his group reported an advanced SPR biosensor for detecting cancer cells [22]. This group also presented another biosensor for Hemoglobin detection [23].…”
Section: Introductionmentioning
confidence: 99%